Influence of long period stacking ordered phase arrangements on the corrosion behaviour of extruded Mg97Y2Zn1 alloy. (June 2016) - Pérez, P.; Cabeza, S.; Garcés, G.; Adeva, P.
Abstract: The influence of second phase arrangements on the corrosion resistance of extruded Mg97Y2Zn1 alloy has been evaluated in a 0.1 M NaCl solution. The microstructure of the alloy consists of a high volume fraction of coarse elongated particles of a long period stacking ordered phase aligned along the extrusion direction. Corrosion rate of transversal sections is lower than that of longitudinal sections. Such difference is attributed to the different orientation of second phases in longitudinal and transversal sections. The corrosion front advances mainly perpendicular to the surface in transversal samples while perpendicular and lateral growth occur in longitudinal samples.